PENGGUNAAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH TERHADAP KINERJA PEGAWAI PADA SATUAN KERJA PERANGKAT DAERAH - Marga Kesumman, Pravitri; Sadha Suardikha, I Made (E-Jurnal Akuntansi, 2016)
The achieve organizational goals for employee success in achieving the targets, by utilizing the information system. Location of the research at SKPD in Denpasar City Government. Sampling technique using purposive sampling and samples used were 64 respondents,and then methods of data collection by spreading questionnaire. Partial Least Squere (PLS) was used to analyze the data. These results indicate the positive influence between computer self-efficacy on perceived usefulness and perceived ease of use, the negative influence between computer anxiety on perceived usefulness and perceived ease of use, computer self-efficacy positive effect on employee performance, there are negative influence in computer anxiety to employee performance, perceived usefulness and perceived ease of use has positive influence to the use of information systems, information systems use a positive effect on employee performance, and the positive influence between  perceived usefulness and perceived ease of use to employee performance mediated the use of information systems.
Keywords: perceived usefulness, computer anxiety, employee performance